Buying Out? – Purchases of Domestic Services and Swedish Women’s Housework Shares - Brånsjö,Linnea (2026)
In order to enhance understanding of what factors influence the gender division of housework, this study investigates the association between households’ purchases of domestic services and women's share of unpaid domestic labour in Swedish heterosexual working couples. Findings from logistic regression analyses suggest that purchases of domestic services, in the literature sometimes also referred to as ‘domestic outsourcing’, have no significant effect on the gender division of unpaid domestic labour. Women in the sample (N = 2,007) were found to be 3.1 % less likely to do the majority of the housework in outsourcing households when other influential factors were taken into account, and male respondents’ (N = 1,630) female spouses were 1.3% less likely to do so. These minor differences were not statistically significant, meaning that they might be products of chance. I thus find no support for Gupta’s autonomy hypothesis, according to which domestic outsourcing is a way for high-income women to buy out of unequal housework sharing arrangements. Findings are instead in line with theoretical expectations from West and Zimmerman’s doing-gender perspective. The results from this analysis further cast doubt on the potential of state funded subsidies for purchases of domestic services to facilitate more gender equal housework sharing practices in the households receiving such subsidies.
Keywords: Housework; Domestic Work; Household Labour Division; Paid Domestic Services; Domestic Outsourcing; Gender; Sweden